Planetary health research: insights from The Lancet Planetary Health original articles. (20th October 2021) - Cadeddu, C; Pezzullo, AM; Sapienza, M; Castagna, C; Regazzi, L; Carini, E; Messina, R; Silenzi, A; Villani, L; Damiani, G; Ricciardi, W
Abstract: Background: In 2017, the Lancet group launched The Lancet Planetary Health to promote the dissemination of research conducted in this field. Planetary health was also extensively discussed during the World Congress on Public Health 2020, which underlines the strategic importance recognized to this topic by experts and researchers active in public health at an international level. The aim was to investigate the role of public health university departments in the field of planetary health. Methods: The Lancet Planetary Health database was queried from the inception to February 2021, to retrieve original articles or reviews whose first and/or last author was affiliated to a University Department of Public Health worldwide. We used the twenty-six EUPHA operational sections to define the research areas of the identified articles. The following data were extracted: study design, EUPHA area, research question, topic, identified gaps in the literature, and key concepts. Results: Out of 543 entries, 44 original articles and reviews were included. Thirty-two percent studies were conducted in Asia, 20% in America, 13% in Europe, 8% in Oceania, 4% in Africa while 23% in a multicentric global context. The area investigated was mainly environmental and health (68%) followed by infectious disease control (14%). Collaboration across different disciplines is highly present in the authorships. Regarding the study design, 30% of the included articles were cohort studies. Conclusions: From 2017 till February 2021, the number of studies performed by public health researchers published on The Lancet Planetary Health is gradually increasing. Since published articles take advantage of the typical research methods and topics of public health and environmental health research, public health university departments can contribute to planetary health science if they seek transdisciplinary collaboration and adopt a planetary health vision.